2021
DOI: 10.1039/d0gc04270f
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-flow step-economical synthesis of thiuram disulfides via visible-light photocatalytic aerobic oxidation

Abstract: A continuous-flow photocatalytic synthesis of the industrially important thiuram disulfides has been developed, utilizing O2 as the oxidant and Eosin Y as the photoredox catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In 2021, Wang et al reported a continuous-flow synthesis of thiuram disulfides, which are functionalities with important industrial applications . Their strategy was based on the eosin Y-mediated photooxidation of the adduct formed between CS 2 and an amine (Scheme ).…”
Section: Flow Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Wang et al reported a continuous-flow synthesis of thiuram disulfides, which are functionalities with important industrial applications . Their strategy was based on the eosin Y-mediated photooxidation of the adduct formed between CS 2 and an amine (Scheme ).…”
Section: Flow Photochemistrymentioning
confidence: 99%
“…In 2021, Wang et al reported a continuous-flow synthesis of thiuram disulfides, which are functionalities with important industrial applications. 522 Their strategy was based on the eosin Y-mediated photooxidation of the adduct formed between CS 2 and an amine (Scheme 76). Although the authors proposed a mechanism involving the superoxide radical (O 2 ) −• , experiments with diphenylisobenzofuran, which is a singlet oxygen trapping agent, proved that singlet oxygen is involved in the mechanism, as claimed by the authors.…”
Section: Singlet Oxygen-mediated Oxidationsmentioning
confidence: 99%
“…Notably, the theoretical capacity of organosulfide could be further improved by devising the end caps and increasing the number of linear S atoms. [ 20 ] The electrode‐level energy density was 376.2 Wh kg −1 , which was the highest among sulfide‐based ASSBs but the second highest when compared with SPE‐based ASSBs. This is due to the lightweight properties of SPEs compared with sulfide electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of dehydrogenative coupling of benzyl mercaptan to form disulfides, the superoxide radical is a very critical free radical species. 52 With the stepwise addition of p -benzoquinone as a radical scavenger, the corresponding photocatalytic activity gradually weakened, indicating that the photoreaction process involves a radical pathway (Fig. S20†).…”
Section: Resultsmentioning
confidence: 99%